Preparation, Physicochemical Characterization and In-Vitro Dissolution Studies of Ketoprofen Solid Dispersion with PEG 6000 and HPMC 6 cps (Bangladesh Pharmaceutical Journal, 2020)
Ketoprofen [2-(3-benzoylphenyl)-propionic acid], a non-steroidal anti-inflammatory drug exhibits poor dissolution pattern. Solid dispersion (SD) techniques were used because it is particularly promising to improve the oral absorption and bioavailability of BCS Class II drugs. This investigation entails solid dispersion of ketoprofen which was formulated and characterized for better release profile and immediate action of the drug. Melting method was applied to prepare solid dispersion by using two immediate release (IR) polymer PEG 6000 and HPMC 6 cps at different weight ratios. In the formulation, a fixed amount of lactose was used as adsorbent. The solid dispersions were investigated for drug entrapment efficiency and dissolution behavior. In vitro dissolution study was performed in phosphate buffer (pH 7.4) medium for one hour. Percent cumulative drug release from solid dispersion was found to be minimum 92.19% and maximum 98.95% within one hour, which showed a better dissolution compared to the active drugs. Evaluation of the properties of the solid dispersion was also performed by using Scanning Electron Microscopy (SEM) study and Differential Thermal Analysis (DTA). SEM results indicated that ketoprofen crystallinity in SDs was significantly reduced, and that the majority of ketoprofen was in amorphous form. No interaction was found between drug and polymers from DTA and Fourier-transform infrared (FTIR) spectroscopy analysis. So, solid dispersion technique may be an effective technique to enhance dissolution rate of ketoprofen.Bangladesh Pharmaceutical Journal 23(1): 44-53, 2020